Hubungan Tingkat Stres dengan Kadar Gula Darah pada Penderita Diabetes Melitus: Relationship Between Stress Levels and Blood Sugar Levels in Diabetes Mellitus - Nurhidayati Tarwadi, Anggi; Nu'im Haiya, Nutrisia; Aspihan, Moch (Universitas Ngudi Waluyo, 2025)
The stimulation of ACTH release due to stress triggers the adrenal glands to release cortisol hormone, which causes an increase in blood glucose levels in patients with diabetes mellitus. This study aims to determine the relationship between stress levels and blood sugar levels in diabetes mellitus patients at RS Bhakti Asih Brebes. This quantitative research uses a descriptive correlational method with a cross-sectional approach. The sample collected consisted of 62 diabetes mellitus patients using purposive sampling technique. The stress level was measured using the valid and reliable Perceived Stress Scale (PSS) questionnaire, while the patients' blood glucose was measured using a calibrated glucometer. The analysis conducted used the Spearman rank test to determine the relationship between stress levels and blood sugar levels. The results found that 28 patients (45.2%) had moderate stress levels and 34 patients (72%) had poor blood sugar levels. There is a significant relationship between stress levels and blood sugar levels with a value of 0.0001 and a correlation strength of 0.740. Conclusion: There is a statistically significant correlation between stress levels and blood glucose levels in diabetes mellitus patients at RS Bhakti Asih Brebes. The lighter the level of stress experienced by the patients, the better the blood sugar levels in diabetes mellitus patients.